Genetics of yield and yield components in pumpkin (Cucurbita moschata) - MOHANTY, B K; MOHANTY, S K; MISHRA, R S (The Indian Journal of Agricultural Sciences, 2013)
An experiment was conducted during 1994-95 to study an 8 Ã— 8 half diallel cross of pumpkin (Cucurbita moschataDuch.ex.Poir.)for yield and its attributing traits at 2 locations. The pooled analysis revealed pre-ponderance of dominanceand non-additive gene action for all the characters supported by low heritability in narrow sense. Pronounced epistasiswas observed for number of female flowers and fruits, average fruit weight and yield/plant. Over dominancewas prevalent for all the traits. Frequent occurrence of dominant genes among parents for vine length and flesh thickness and recessivegenes for the remaining characters were indicated. Most dominant genes exerted positive effect. However, unequal distributionof positive and negative alleles showing dominancein parents was recorded for all the characters except number of primarybranches/plant. Polygenic inheritance of yield and yield contributing characters were detected. Heterosis breeding was suggestedfor improvement of yield and yield components in pumpkin.